THE SHIPWRECK OF ANTHROPOCENTRISM: RETHINKING LAW FROM THE OCEAN (CIPEEX, 2026)
This study promotes a critical analysis of the relationship between law and aquatic ecosystems, arguing that traditional legal dogma, with its anthropocentric matrix, is insufficient to achieve the objectives of SDG 14 (Life Below Water). Based on the inherent contradiction in this goal—which simultaneously proposes economic exploitation and resilient protection of the seas—the study argues for the need for a paradigm shift. Using the film Piranha (1978) as a case study, it demonstrates how pop culture exposes the flaws of a legal system that, by ignoring the contingency and dangers of a risk society, becomes an instrument of degradation. As an alternative, it proposes an approach based on Post-Humanist Law, which decentralizes the human figure, recognizes the intrinsic value of non-human life, and adopts contingency as a method for more flexible, adaptive, and truly protective environmental governance.
Keywords: post-humanist law; ODS 14; risk society; contingency; pop culture; anthropocentrism; marine environmental law